The Coccinellidae (Coleoptera) from Fuerteventura, Canary Islands - Romanowski, Jerzy; Ceryngier, Piotr; Větrovec, Jaroslav; Szawaryn, Karol (Zootaxa, 2019)
During this study, Coccinellidae were collected and observed at 25 sites located along the coast and inland of the island of Fuerteventura during 2016 and 2017. A total of 2825 Coccinellidae specimens belonging to 22 species was recorded, of which 11 species are newly recorded from Fuerteventura. In the case of three species taxonomical decisions are proposed. Scymnus incisus (Har. Lindberg, 1950) is transferred to the genus Nephus Mulsant and placed in the nominate subgenus as Nephus (Nephus) incisus (Har. Lindberg, 1950), comb. nov. Scymnus medanensis Eizaguirre, 2007, is redescribed and placed in the subgenus Pullus Mulsant. Coccinella algerica Kovář, 1977, is synonymized with Coccinella septempunctata Linnaeus, 1758, syn. nov. We propose retaining the taxonomic distinction of the North African and Canarian populations of this species as the subspecies Coccinella septempunctata algerica Kovář, stat. nov. Nephus peyerimhoffi (Sicard, 1923) is deleted from the list of ladybird beetles inhabiting the Canary Islands.